Pengaruh Limbah Tahu Terhadap Kualitas Air Sungai Cikeruh dan Penanganannya dengan Metode Adsorpsi Berdasarkan Prinsip Teknologi Tepat Guna - TURSINA HAJAR; ADI MULYANA SUPRIATNA; EKO PRABOWO HADISANTOSO (Gunung Djati Conference Series, 2022)
This study aims to analyze the condition of the water quality of the Cikeruh River in terms of BOD, COD, TSS, and pH parameters, analyze the effect of liquid waste from the Homemade Tofu Industry in Ds. Mekarsari on the water quality of the Cikeruh River in terms of BOD, COD, TSS, and pH parameters, to determine the effectiveness of adsorption with the principle of Appropriate Technology (TTG) in reducing pollutant levels of liquid waste from the Homemade Tofu Industry, Ds. Mekarsari. The sampling technique used is the grab sample. The results of the analysis show that the condition of the water quality of the Cikeruh River is based on the quality standard of PP RI No. 22 of 2021 for river water points before being polluted with liquid waste from the Tofu Industry in accordance with quality standards, while after being polluted with liquid waste from the Tofu Industry the levels of COD and TSS exceed the quality standards. The results show the liquid waste from the Tofu Industry with a pH parameter of 4.35, a COD level of 1128 mg/L, and a TSS level of 595 mg/L. This level exceeds the specified quality standard, so it can pollute the Cikeruh river. Therefore, it is necessary to treat it first before the wastewater is discharged into the river. The results of the analysis show that liquid waste from one of the Tofu Industries in Mekarsari Village which has been tested with the adsorption method based on the principle of Appropriate Technology filter combination of rice husk ash, coconut shell charcoal, pumice stone, and red brick sand is able to reduce the levels of pollutant parameters from the COD parameters and This TSS is proven by the average percentage of effectiveness obtained after treatment for COD levels of 51.42%, TSS levels of 65.71%, while for pH neutralization it is 7.5%.